Electronic Payment Systems Reduce Informal Cash Holdings and Strengthen Iraqi Economic Stability - Mohammed Madlool Ibrahim; Abdullah Muhammad Rashid Al-Ramli; Sabah Ahmed Asmaeel (Indonesian Journal of Law and Economics Review, 2026)
General Background: Cash dominance and low financial inclusion constrain monetary control in developing economies. Specific Background: In Iraq, extensive cash circulation outside banks has weakened monetary policy during 2010–2024 despite expanding electronic payments. Knowledge Gap: Empirical evidence on how electronic payment adoption affects informal money supply and macroeconomic outcomes in Iraq remains limited. Aims: This study examines the relationship between electronic payment methods and cash outside the banking system and their macroeconomic effects. Results: Expanded electronic payments correlate inversely with informal cash, improving financial inclusion and monetary policy efficiency. Novelty: It provides a long-term Iraqi case analysis linking digital payments to informal money reduction. Implications: Strengthening payment infrastructure and supportive legislation can enhance monetary stability and economic growth.Keywords : Electronic Payment Systems, Informal Money Supply, Financial Inclusion, Monetary Policy Effectiveness, Iraqi Banking SectorHighlight : Electronic payment adoption shows inverse relationship with informal cash circulation in Iraq's banking system. Weak banking infrastructure and low public trust hinder digital payment expansion despite government initiatives. Financial inclusion remains insufficient with only 2.67 bank branches per 100,000 adults by 2024.